PELATIHAN AKURASI KODING PADA KASUS-KASUS PENDING KLAIM OBSTETRI DI RSIA CICIK PADANG - Yastori Yastori; Nurul Fitri Khumaira (LPPM Universitas Bina Bangsa, 2024)
Pending claims cases are a problem that often occurs in hospitals, especially in the JKN era because they are related to hospital finances. Based on a preliminary survey, it is known that there are still pending claims almost every month with an average number of cases of 3-5 cases per month. Coding problems in Obstetrics cases that occur are like PROM cases which are problematic if KPD can be coded if it lasts more than 6 hours and there is no opening in the mother about to give birth. Apart from that, in cases of PEB, attention must be paid to the patient's blood pressure, the presence of 40% Magnesium Sulfate, increased proteinuria and undiagnosed hypertension before pregnancy. Pending cases that occur include confirmation regarding coding accuracy, whether the requirements and procedures provided have been met and whether the attached documents are complete. The aim of this PKM is to provide training for medical record officers so that they can optimize their ability to provide accurate codes so that pending cases can be minimized. The PKM method is the lecture, socialization, discussion and case discussion method. The activity was held on Tuesday, May 28 2024 at RSIA Cicik Padang. The activity went smoothly, and it is known that the coders have begun to understand how coding regulations are based on ICD-10, the implementation of BPJS regulations and what pending cases often occur. This can be seen from the results of discussions between coders, medical records officers and the PKM chairman. In the future, it is recommended that RSIA Cicik provide coders per inpatient and outpatient department, implement coding SOPs properly, carry out performance evaluations and organize BPJS claims and pending cases. It is recommended that future PKM activities be able to discuss pending Obstetrics cases and the amount of financing that is pending due to these pending cases